Od semiotike k pragmatizmu - Lobnik, Alja (Amfiteater (Ljubljana), 2016)
The antagonism of a thought as an event - as proposed by Deleuze - and a thought as representation is a line of thinking that makes a diversion from semiotics, the basic model of the 20th century theory of theatre, and instead applies a genealogical approach. The article addresses "new drama" on the basis of this tradition which poses the following question: "How to think the relation between the text and the event beyond representation?" Due to the intertwinement of the text and eventness - the texts are produced considering their performativity, with a clear knowledge of the theatre dispositif, they are produced within or by the event - such changes blur the liminality of the texts and their autonomous status. Investigating the relation between practice and knowledge, we are interested in whether there exists a sufficient conceptual apparatus within the literary/theatrical theory that would reflect literary originality, transgressiveness (across some classical drama postulates), liminality (between theatre and literature) and, in particular, the eventness of "new drama". Following the tradition of the (French) score of thought - Althusser, Deleuze, Massumi - the article focuses on the textual practices of new drama and theoretical shifts, their immanent liaison and a reflection on the academic disciplines that have - when confronted by interventions of theory and practice - been compelled to re-evaluate their autonomy and ontology.
Keywords: eventness; genealogija; genealogy; gledališče; gledališka semiotika; gledališka teorija; materialism; materializem; new drama; nova dramatika; semiotics; theater